Alkaline oxygen evolution - Singh, A K; Ji, S; Singh, B; Das, C; Choi, H; Menezes, P W; Indra, A (Elsevier Ltd, 2021)
Herein, we report a Mott-Schottky catalyst by entrapping cobalt nanoparticles inside the N-doped graphene shell (Co@NC). The Co@NC delivered excellent oxygen evolution activity with an overpotential of merely 248 mV at a current density of 10 mA cm–2 with promising long-term stability. The importance of Co encapsulated in NC has further been demonstrated by synthesizing Co nanoparticles without NC shell. The synergy between the hexagonal close-packed (hcp) and face-centered cubic (fcc) Co plays a major role to improve the OER activity, whereas the NC shell optimizes the electronic structure, improves the electron conductivity, and offers a large number of active sites in Co@NC. The density functional theory calculations have revealed that the hcp Co has a dominant role in the surface reaction of electrocatalytic oxygen evolution, whereas the fcc phase induces the built-in electric field at the interfaces with N-doped graphene to accelerate the H+ ion transport.
exploring synergy between fcc and hcp cobalt nanoparticles entrapped in N-doped graphene
This work was financially supported by CSIR Grant no. 01(2977)/19/EMR-II ), Govt. of India. B.S. acknowledges the research fellowship from DST-INSPIRE ( 180147 ). H.C. and S.J. acknowledge the financial support from the Federal Ministry of Education and Research under the “Make Our Planet Great Again-German Research Initiative” (MOPGA-GRI; 57429784 ) implemented by the German Academic Exchange Service: Deutscher Akademischer Austauschdienst (DAAD). P.W.M. acknowledges support from the German Federal Ministry of Education and Research in the framework of the project Catlab ( 03EW0015A/B ).
Keywords: Co nanoparticles; Core-shell structure; Nitrogen doped graphene; Phase effect; Water oxidation